The neural impact of editing on viewer narrative cognition in virtual reality films: eye-tracking insights into neural mechanisms - Zou, Qiaoling; Zheng, Wanyu; Su, Zishun; Zhang, Li; Zhuo, Ziqing; Li, Dongning (Frontiers in Psychology, 2025)
IntroductionThe development of virtual reality (VR) films requires novel editing strategies to optimize narrative cognition in immersive environments. While traditional film editing guides attention through controlled sequences of shots, the interactive nature of VR disrupts linear storytelling, challenging creators to balance emotional experience and spatial coherence. By combining eye-tracking technology with neuroscientific findings, this study aims to investigate how different editing techniques in virtual reality (VR) films affect viewers’ narrative cognition, focusing on visual attention, emotional experience and cognitive load, and to optimize VR film editing strategies through a neurocognitive lens.MethodsA controlled experiment with 42 participants was conducted using three versions of a VR movie: an unedited movie, a hard cut edited movie, and a dissolve-transition edited movie. Eye-tracking metrics were recorded using the HTC Vive Pro Eye headset, and emotional experiences were assessed using post-viewing questionnaires. Data were analyzed using SPSS and visualized using heat maps and trajectory maps.ResultsThe unedited movie (F1) elicited the highest visual attention (TDF: M = 18,953.83 vs. F2/F3, p < 0.001) and emotional immersion, with 75% of viewers rating it as “highly immersive.” It also showed sustained activation in areas related to emotional engagement. Edited movies, both hard cuts (F2) and dissolve-transitions (F3), reduced cognitive load (TSD: M = 16,632.83 for F1 vs. 15,953.18 for F3, p < 0.01) but resulted in fragmented attention. Dissolve-transitions (F3) decreased viewer enjoyment (APD: M = 0.397 vs. F1, p < 0.001). One-way ANOVA analysis revealed that seamless editing enhanced emotional coherence, while abrupt cuts disrupted spatial and temporal integration, leading to reduced emotional engagement.DiscussionUnedited VR films promote emotional coherence driven by the amygdala and maintain attention stability mediated by the prefrontal cortex, which enhances immersive narrative cognition. In contrast, editing techniques prioritize cognitive efficiency at the expense of emotional experience. To maintain immersion, filmmakers should focus on seamless transitions, while strategically using edits to direct attention in the complex 360° environment of VR. These findings contribute to neurocinematic theory by connecting the neural dynamics induced by editing with behavioral outcomes, offering practical insights for VR content creation.